Theaters of pardoning - Meyler, Bernadette (Corpus juris (Ithaca, N.Y.), 2019)
"This book aims to address the roots of pardoning's treatment in contemporary politics and uncover what new formulations of pardoning might contribute by examining what it calls "theaters of pardoning"--A form of tragicomedy--in the drama and politics of seventeenth-century England"--